Anti-Trop2 blockade enhances the therapeutic efficacy of ErbB3 inhibition in head and neck squamous cell carcinoma - Redlich, Nathan (Cell Death Dis, 2018)
ErbB3 has been widely implicated in treatment resistance, but its role as a primary treatment target is less clear. Canonically ErbB3 requires EGFR or ErbB2 for activation, whereas these two established treatment targets are thought to signal independently of ErbB3. In this study, we show that ErbB3 is essential for tumor growth of treatment-naive HNSCC patient-derived xenografts. This ErbB3 dependency occurs via ErbB3-mediated control of EGFR activation and HIF1α stabilization, which require ErbB3 and its ligand neuregulin-1. Here, we show that ErbB3 antibody treatment selects for a population of ErbB3-persister cells that express high levels of the transmembrane protein Trop2 that we previously identified as an inhibitor of ErbB3. Co-treatment with anti-ErbB3 and anti-Trop2 antibodies is synergistic and produces a greater anti-tumor response than either antibody alone. Collectively, these data both compel a revision of ErbB-family signaling and delineate a strategy for its effective inhibition in HNSCC.